Remote nuclear microreactors: a preliminary economic evaluation of digital twins and centralized offsite control - Bryan, Haydn C.; Jesse, Katherine W.; Miller, Charles A.; Browning, Jeren M. (Frontiers in Nuclear Engineering, 2023)
The nuclear energy industry is looking to next-generation reactor designs to augment, diversify, and expand generation capacity in an increasingly complex and varied energy landscape. A key element in this objective is microreactors—small nuclear reactors which can provide flexible capacity at a reduced scale compared to traditional large-scale nuclear reactors. Specifically, microreactors could be used to provide clean, reliable combined heat and power to remote communities, worksites, or facilities. However, the construction and operations and maintenance costs to supply the required operator staffing and physical supporting assets, such as control rooms, could be a limiting factor for first adopters of the technology. Opportunities to reduce the cost of monitoring and control activities could enable early adoption, allowing economies of learning to take effect, spurring further adoption. A reduction in the number and cost intensity of control rooms and operators per deployed microreactor could significantly decrease the overall cost for a fleet of microreactors. To optimize microreactor economic competitiveness, one solution would be to establish an off-site operation facility for centralized monitoring and control (CM&C) of a fleet of microreactors. Leveraging advances in digital instrumentation and control systems could bolster the safety, reliability, and security of the remote communication architecture inherently required to operate remotely. Digital twins (DTs) are virtual replicas of physical assets which can be used for a variety of applications, including analyzing I&C signals against a validated model to perform several analysis and prediction functions. When implemented properly, DTs can potentially detect anomalies and component failures, and serve as a diagnostic tool for operators. These technologies can enhance operator understanding and awareness, reduce the management demand time on operators, and increase asset uptime by providing early alerts for failures alongside insights to aid in predictive maintenance. Furthermore, a DT system could enhance the secure and reliable communication architecture necessary for remote microreactor operation by verifying signals and suggesting or automating controls, thereby boosting their economic viability. This research examines the economic effects of various control strategies ranging from many individually and on-site controlled reactors to co-management of all microreactors in a system from a single, off-site control center. Results from the analysis are positive, revealing significant cost-reduction opportunities.